Avaliação da estabilidade de cor de botões de íris artificiais variando a cor e as técnicas de obtenção em prótese ocular antes e após polimerização da resina acrílica - Oliveira, Kamila Freitas [UNESP] (2012)
Ocular prosthesis is responsible for recovering the esthetics and self-esteem of the user. It is known that the most affects the longevity of ocular prostheses is the instability of the artificial iris color, due to polymerization process of the prosthesis and clinical use. This study investigated the effect of three different techniques of ocular prosthesis fabrication on the color change of the artificial iris button for two-tone color before and after the polymerization of the colorless resin. A total of 60 samples were made by simulating artificial eyes. Half of the samples were made with blue color artificial iris and half were made with sepia color artificial iris. For each color, ten samples of each technique (conventional (CE), prefabricated cap technique (PC) and inverted painting (IP)) were made. The artificial iris color measurement was conducted through reflection spectrophotometry using the CIE L*a* b* system before and after prosthesis (colorless resin) polymerization. Data were evaluated by ANOVA and the Tukey HSD (Honestly Significantly Different) (α=0.05). All the samples exhibited color changes. PC exhibited the highest color change values for both the artificial iris color (P<.05). IP exhibited the lowest color change values for sepia artificial iris color (P<.05). Sepia artificial iris color exhibited the lowest color change values, statistically significant, compared to blue color artificial iris, for both techniques (P<.05). The different techniques used to obtain ocular prosthesis significantly affected the stability of artificial iris color for each color-tone